Potential Health Benefits and Risks Associated with Calisthenics, a Sport of Increasing Popularity – A Literature Review - Werenkowicz, Wiktor; Boral, Aleksandra; Czarnecki, Bartłomiej; Kryś, Dominika; Koczur, Julia; Górski, Michał; Pniok, Wiktoria; Kurkiewicz, Wojciech; Brzoza, Joanna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Calisthenics is a sport in which the load and resistance is the body of the person exercising. It can be practiced indoors or in outdoor gyms, and to perform exercises such as pull-ups, push-ups, jumping jacks and lunges, no special equipment is needed or only basic equipment in the form of a bar and parallel bars. Due to the ease of performing most calisthenic exercises, their availability, and the health benefits of practicing it, its popularity is constantly growing among people of all ages. The purpose of this article is to collect information on the possible health benefits of calisthenics and the most common injuries associated with practicing it. A brief description of the state of knowledge: During calisthenics training using your body weight, people who exercise face a number of mental and physical challenges that depend on the level of advancement of the exercise or gymnastic figure being performed. During calisthenics training using your body weight, exercisers face a number of mental and physical challenges that depend on the level of advancement of the exercises or gymnastic figures performed. These exercises can lead to health benefits as well as injuries. Injuries during body weight exercises can affect any limb. The most common joints that are injured are the knee, shoulder, or wrist joints. The health benefits of this type of exercise are many, both physical, such as reduced cardiovascular risk and muscle growth, and mental, such as reduced anxiety, a lower chance of depression and better sleep. Conclusions: The risk of injury during calisthenics is relatively low, and the health benefits of the exercises are undeniable. Calisthenics is a good choice for people who do not want to spend a lot of money on equipment or a gym membership and want to improve their physical and mental health with a low risk of serious injuries.